GENETIC AND MORPHOLOGICAL CHARACTERIZATION OF LEBANESE MOUNTAIN LOCAL GOAT POPULATION - T. Mira1; Abi-Rizk Alain; A. Charbel; A. S. Saab (Journal of Animal and Plant Sciences, 2020)
Lebanese mountain Baladi goats are endemic to Lebanon. However, few available genetic data on Baladi population is available. Information based on morphological and biochemical markers exists but yet remains imprecise. The aim of this study is to characterize the morphological and genetic traits of the Lebanese mountain Baladi population. The experiment was carried out in two different regions: Deir El Ahmar(1450m) and Boksmaya (400m). A total of 47 does, aging between 2-3 years, were studied; 9 quantitative traits and 5 qualitative traits were measured on each doe. The doe’s genomic DNA was extracted and amplified by using PCR with a panel of 10 ISSR microsatellite markers along with collecting phenotypic data from each animal. The results revealed the presence of two main clusters both genetically and morphologically: CI and CII where most of CI animals produced a lower quantity of milk compared to CII. The mean value for all quantitative traits, except barrel length, showed a superior significant difference between groups (p≤0.05). A positive correlation between the percentage of polymorphism, quantity of milk, ears and head color in both groups was observed. This attempt was to genetically characterize Lebanese Baladi population and to correlate its phenotype with its genotype.
Keywords: Baladi goat; genetic; genotype; ISSR; phenotype